Estudos funcionalistas no Brasil - Neves, Maria Helena de Moura (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
The paper presents a comprehensive survey of functional research in Brazil, from the very beginning, reaching research groups and individual researchers, carefully distinguishing the theoretical approaches followed. An extensive list of published work is added. (AE)